Material characterization and electrical performance of Prosopis africana conductive ink for antenna applications - Babani, Suleiman; Hamidon, Mohd Nizar; Ismail, Alyani; Jaafar, Haslina; Hasan, Intan Helina; Shafee, Farah Nabilah; Shitu, Ibrahim Garba; Lamido, Jamila; Lawan, Sani Halliru; Yunusa, Zainab (Universiti Putra Malaysia Press, 2025)
This research explores the development and evaluation of a bio-based conductive ink derived from Prosopis Africana Char (PAC) for antenna applications, aiming to provide a sustainable, cost-effective alternative to conventional conductive materials in electronics. The study focuses on the structural, thermal, and electrical properties of the PAC-based ink to determine its suitability for printed antenna technology. The conductive ink was formulated by mixing PAC powder with an organic binder composed of m-xylene, linseed oil, and α-terpineol in a 45:55 wt% ratio, followed by mechanical stirring at 250 rpm for 3 hours at 40 °C to achieve a homogeneous paste. This mixture was screen-printed onto an FR4 substrate and thermally treated at 300 °C. Characterization techniques such as field emission scanning electron microscopy (FESEM), Raman spectroscopy, thermogravimetric analysis (TGA), and four-point probe conductivity measurements were used to analyze the ink's morphology, composition, and electrical behavior. The PAC ink demonstrated a high conductivity of 4.678 S/m, strong adhesion, and excellent printability and environmental stability under variable temperature and humidity. Antenna performance assessments revealed promising results, including a return loss of |S11|= −16.50 dB, a resonant frequency of 9.5 GHz, a bandwidth of 1.32 GHz, a peak gain of 6.62 dB, a VSWR of 1.25, and an efficiency of 80%. These outcomes indicate that the PAC thick film enhances bandwidth and radiation efficiency due to its favorable dielectric characteristics. Overall, the study confirms the potential of Prosopis africana as a viable, eco-friendly conductive material for flexible, lightweight antennas, offering a promising direction for sustainable innovation in wireless communication technologies.